Examining Dual-Moderation of Structure Racism, Economic Fragility, High Tech Startup’s Team Diversity and Performance - Saeed Mousa (iRASD Journal of Management)
This study has been conducted to examine the dual moderation of structural racism and economic fragility between team diversity and startup team performance. Team diversity is particularly important for new ventures or startups as the need or focus of such startups is on a diverse range of consumers. The role of racism and economic fragility cannot be ignored in this regard. To conduct this research the targeted population is the high-tech startups in France. For data collection, 351 questionnaires were received and processed for data analysis. The results indicated a significant impact of team diversity on startup team performance. The moderating role of structural racism was also significant between team diversity and startup team performance. Whereas, economic fragility also significantly moderates the relationship between team diversity and startup team performance. The practical importance of this study is greatly implied in those startups which incorporate diversity in their workplace. The policymakers are also devoted to performing their part concerning the policies that are being formulated to encourage and promote diversity in the workplace as well as in educational settings. Theoretically, this research contributes to the growing body of literature regarding startup performances. However, most of the high-tech startups in France did not contain the required data for gaining clear facts and figures. This limitation can be catered to in the future by targeting more advanced high-tech startups in France.